Analisis Model Pembelajaran Kooperatif Tipe STAD Dengan Media Pembelajaran Ular Tangga Terhadap Minat Belajar - Pipit Putri Hariani MD; Agus Wiranda; Ijah Mulyani Sihotang (-)
The purpose of this study was to analyze the effect of snake and ladder learning media using the STAD type cooperative learning model in increasing interest in learning. This study uses primary data sources in the form of reference studies that are used as the main source of research references, the primary sources used are journals related to the research title, namely the Snakes and Ladders learning media journal model using the STAD Type Cooperative Learning Model in increasing interest in learning and other related references. Based on the results of the study that the author conducted on 10 previous research journals, it was found that the use of the snake and ladder educational game tool through the STAD type learning model can make students more active so as to increase interest and learning achievement. The conclusion from the research is that the activeness of students during learning shows a very active category. Of the 10 research journals studied that student learning outcomes were significantly different between before and before treatment. Based on the results of the validity of data from several previous studies regarding the use of snakes and ladders media through the STAD type learning model can increase student interest and learning outcomes by 90%.